Reactivation of Pulmonary Tuberculosis After 64 Years: Case Report - Carrillo-Vázquez, Carolina; Dzul-Caballero, José Emmanuel; May, Valeria Guadalupe Sonda (British Journal of Healthcare and Medical Research, 2024)
Introduction: Pulmonary tuberculosis is a disease with a very high prevalence worldwide, caused by Mycobacterium tuberculosis (MTB). There are several risk factors associated with the development and clinical expression of this disease. Culture remains the gold standard for the diagnosis of tuberculosis, the IDSA recommends obtaining three samples for bacilloscopy. It is possible to exclude the diagnosis if acid-resistant bacilli are not detected in samples of adequate quality within three days, which may be microscopy of sputum, bronchial secretion or bronchoalveolar lavage fluid. Clinical case: A 78-year-old female with respiratory symptoms, who had a history of pulmonary tuberculosis in adolescence. Imaging studies revealed multiple caverns and there was a suspicion of bacterial infection of the same. He received multiple antimicrobial regimens with worsening of the symptoms, and it was necessary to perform a bronchoscopy for alveolar lavage obtaining samples, with the result of tuberculosis disease. Discussion: The reactivation of tuberculosis is due to multiple factors that can generate immunosuppression. Sometimes, due to the lack of obtaining adequate samples, it is not possible to reach an accurate diagnosis, leading to the inappropriate use of antimicrobials and increasing the risk of resistance, as well as the misuse of resources and increasing health expenditure. Conclusions: Tuberculosis remains a very prevalent disease in Mexico and its diagnostic suspicion must be high. The difficulty that sometimes exists in isolating the bacteria is well known; however, diagnostic resources should be exhausted when the suspicion of its isolation is high.